(untitled) (PerCursos, 2021)
The emergence of America is marked by controversies and by the covering up of memory and the other (Native Americans). In this perspective, this article seeks to outline an analysis of the reports of colonization, from which the figure of the Indian and his associations are created. For this, the text was divided into 5 axes. Firstly, the Salvationist myth of the good savage and the initial narrative of colonization stand out. Afterwards, it is evident that the ’Amerindian’ native is decarcerated from his humanity in order to justify his exploration in the face of the New World, a fact related to the myth of modernity and the cover-up of multiplicity, which make up the third point of approach. In the fourth point, the strategy of domination present in the nomination “Indian” adopted by the Europeans to refer to the natives stands out. In the fifth point highlighted, the myth of the encounter between races that masks violence and strategies of domination of the territory is emphasized. Finally, the text ends, making a dive, submersion and emergence of the topics and points covered. We conclude that the history of the American peoples and the historiography of colonization need to be revisited in order to enhance the perception of the other side of the arrival of Europeans and the cover-up and devaluation of the memory of the peoples of America.